Genome-wide identification, evolution and expression analysis of bone morphogenetic protein (BMP) gene family in chinese soft-shell turtle (Pelodiscus sinensis) - Lei, Luo; Zhu, Junxian; Chen, Chen; Wang, Yongchang; Wu, Congcong; Qi, Ming; Wang, Yakun; Liu, Xiaoli; Hong, Xiaoyou; Yu, Lingyun; Chen, Haigang; Wei, Chengqing; et al. (Frontiers in Genetics, 2023)
Introduction: Bone morphogenetic proteins (BMPs) play a crucial role in bone formation and differentiation. Recent RNA-Seq results suggest that BMPs may be involved in the sex differentiation of P. sinensis, yet more relevant studies about BMPs in P. sinensis are lacking. Methods: Herein, we identified BMP gene family members, analyzed the phylogeny, collinear relationship, scaffold localization, gene structures, protein structures, transcription factors and dimorphic expression by using bioinformatic methods based on genomic and transcriptomic data of P. sinensis. Meanwhile, qRT-PCR was used to verify the RNA-Seq results and initially explore the function of the BMPs in the sex differentiation of P. sinensis. Results: A total of 11 BMP genes were identified, 10 of which were localized to their respective genomic scaffolds. Phylogenetic analysis revealed that BMP genes were divided into eight subfamilies and shared similar motifs (“WII”, “FPL”, “TNHA”, “CCVP”, and “CGC”) and domain (TGF-β superfamily). The results of the sexually dimorphic expression profile and qRT-PCR showed that Bmp2, Bmp3, Bmp15l, Bmp5, Bmp6 and Bmp8a were significantly upregulated in ovaries, while Bmp2lb, Bmp7, Bmp2bl and Bmp10 were remarkable upregulated in testes, suggesting that these genes may play a role in sex differentiation of P. sinensis. Discussion: Collectively, our comprehensive results enrich the basic date for studying the evolution and functions of BMP genes in P. sinensis.